Formal Verification of an Autonomous Wheel Loader by Model Checking - Gu, Rong; Marinescu, Raluca; Seceleanu, Cristina; Lundqvist, Kristina (2018 IEEE/ACM 6th International FME Workshop on Formal Methods in Software Engineering (FormaliSE), 2018)
In an attempt to increase productivity and the workers' safety, the construction industry is moving towards autonomous construction sites, where various construction machines operate without human intervention. In order to perform their tasks autonomously, the machines are equipped with different features, such as position localization, human and obstacle detection, collision avoidance, etc. Such systems are safety critical, and should operate autonomously with very high dependability (e.g., by meeting task deadlines, avoiding (fatal) accidents at all costs, etc.). An Autonomous Wheel Loader is a machine that transports materials within the construction site without a human in the cab. To check the dependability of the loader, in this paper we provide a timed automata description of the vehicle's control system, including the abstracted path planning and collision avoidance algorithms used to navigate the loader, and we model check the encoding in UPPAAL, against various functional, timing and safety requirements. The complex nature of the navigation algorithms makes the loader's abstract modeling and the verification very challenging. Our work shows that exhaustive verification techniques can be applied early in the development of autonomous systems, to enable finding potential design errors that would incur increased costs if discovered later.